2022
DOI: 10.1128/msphere.00393-22
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Editing Induces Loss of Heterozygosity in the Pathogenic Yeast Candida parapsilosis

Abstract: CRISPR-Cas9 has greatly streamlined gene editing and is now the gold standard and first choice for genetic engineering. However, we show that in diploid species, extra care should be taken in confirming the cause of any phenotypic changes observed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…gambiae, despite its importance for public health and the successful development of several gene drive strategies in the lab. CRISPR-Cas9 mediated DSBs have been seen to induce GCTs of up to 1.7kb in yeasts (27,28). I-Sce1 mediated DSBs have induced GCTs of up to 0.5kb in mammalian stem cells (29), and up to 0.8kb (average 471bp) in Drosophila melanogaster (30,31).…”
Section: Dna Repair Mechanisms and Gene Drive Homing In Mosquitoesmentioning
confidence: 99%
“…gambiae, despite its importance for public health and the successful development of several gene drive strategies in the lab. CRISPR-Cas9 mediated DSBs have been seen to induce GCTs of up to 1.7kb in yeasts (27,28). I-Sce1 mediated DSBs have induced GCTs of up to 0.5kb in mammalian stem cells (29), and up to 0.8kb (average 471bp) in Drosophila melanogaster (30,31).…”
Section: Dna Repair Mechanisms and Gene Drive Homing In Mosquitoesmentioning
confidence: 99%
“…This can result in loss of heterozygosity (LOH) for extended regions on this chromosome and, consequently, effects on the phenotype of the mutants that are not caused by the deletion of the target gene but by loss of allelic variants of other genes, especially when only one allele is functional ( 4 , 30 48 ). In fact, it has recently been shown that CRISPR-Cas9-based gene editing strongly increased the frequency of LOH in Candida parapsilosis , especially on the target chromosome ( 49 ).…”
Section: Introductionmentioning
confidence: 99%